Restructuring Proceedings - New Regulations in the Polish Economy - Andrzej TOKARSKI (Communications of International Proceedings, 2020)
The problem of the accuracy of choice between the liquidation of an enterprise and its restructuring is one of the main topics of interest for practitioners and theorists dealing with the bankruptcy of enterprises. The decision to restructure constitutes an alternative to declaring an enterprise bankrupt. The article presents kinds of restructuring proceedings taking into account their characteristics, advantages and disadvantages, benefits and threats resulting from the multitude of restructuring proceedings including.
Keywords: Restructuring Proceedings; Restructuring Of Enterprises; Second Chance Policy; Restructuring Law